Exercise induced hypoglycaemic hyperinsulinism - Meißner, Tobias; Otonkoski, Timo; Feneberg, Reinhard; Beinbrech, Beatrice Ursina; Apostolidou, Sofia; Sipilä, I.; Schaefer, Franz; Mayatepek, Ertan (Archives of disease in childhood, 2001)
Hyperinsulinism in childhood is often caused by genetic defects involving the regulation of insulin secretion leading to recurrent episodes of hypoglycaemia. We report two patients with exercise induced hypoglycaemia.